SPEED DEPENDENCE OF ACOUSTIC VIBRATION PROPAGATION FROM THE FERRITIC GRAIN SIZE IN LOW-CARBON STEEL - Vakulenko, I. A.; Nadezhdin, Yu. L.; Sokyrko, V. A.; Hai, Xu Xiao (Science and Transport Progress, 2015)
Purpose. It is determining the nature of the ferrite grain size influence of low-carbon alloy steel on the speed propagation of acoustic vibrations. Methodology. The material for the research served a steel sheet of thickness 1.4 mm. Steel type H18T1 had a content of chemical elements within grade composition: 0, 12 % C, 17, 5 % Cr, 1 % Mn, 1, 1 % Ni, 0, 85 % Si, 0, 9 % Ti. The specified steel belongs to the semiferritic class of the accepted classification. The structural state of the metal for the study was obtained by cold plastic deformation by rolling at a reduction in the size range of 20-30 % and subsequent recrystallization annealing at 740 – 750 ° C. Different degrees of cold plastic deformation was obtained by pre-selection of the initial strip thickness so that after a desired amount of rolling reduction receives the same final thickness. The microstructure was observed under a light microscope, the ferrite grain size was determined using a quantitative metallographic technique. The using of X-ray structural analysis techniques allowed determining the level of second-order distortion of the crystal latitude of the ferrite. The speed propagation of acoustic vibrations was measured using a special device such as an ISP-12 with a working frequency of pulses 1.024 kHz. As the characteristic of strength used the hardness was evaluated by the Brinell’s method. Findings. With increasing of ferrite grain size the hardness of the steel is reduced. In the case of constant structural state of metal, reducing the size of the ferrite grains is accompanied by a natural increasing of the phase distortion. The dependence of the speed propagation of acoustic vibrations up and down the rolling direction of the ferrite grain size remained unchanged and reports directly proportional correlation. Originality. On the basis of studies to determine the direct impact of the proportional nature of the ferrite grain size on the rate of propagation of sound vibrations in the low-carbon alloy steel. The directly proportional nature of influence of ferrite grain size on the speed propagation of acoustic vibrations in low-carbon alloy steel on the basis of the conducted researches is defined. The paper is shown that at increasing in the size of the recrystallized ferrite grain the degree of influence the texture from the previous cold plastic deformation by rolling increases. Practical value. The received results on nature determination of influence of ferrite grain size on the speed propagation of acoustic vibrations can be the useful by development of techniques of non-destructive testing of metal materials quality. The special value the specified technique of measurement acquires in the conditions of line production of metal constructions.